Strengthening Digital Marketing Knowledge and Skills at Cafe and Resto De.Joglo in Jember Regency: Penguatan Pemahaman dan Keterampilan Pemasaran Digital pada Cafe dan Resto De.Joglo di Kabupaten Jember - Eka Larasati; Luluk Fitri Yani (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
The development of digital technology has encouraged culinary businesses to adopt more adaptive and interactive marketing strategies. However, Cafe and Resto De.Joglo in Jember Regency still faced several problems in optimizing digital platforms, including inconsistent social media management, limited promotional content planning, and incomplete business information on digital platforms. This community service program aimed to strengthen the knowledge and skills of Cafe and Resto De.Joglo managers in applying digital marketing as a business promotion strategy. The activity was conducted through four stages: preparation, education, training, and evaluation. The participants consisted of two business managers who were directly responsible for marketing and digital media management. The materials covered basic concepts of digital marketing, social media management, content creation, product photography, Google Business Profile optimization, and the “Post & Get” promotional program. The results showed that the participants gained better understanding of digital marketing concepts, became more capable of preparing simple promotional content, understood the importance of consistent social media management, and started improving business information on digital platforms. The activity also produced an initial digital promotion plan that can be implemented by the partner. However, the impact on business performance, such as customer growth, social media engagement, and revenue, still requires long-term monitoring. Therefore, further assistance and periodic evaluation are needed to ensure sustainable digital marketing implementation.